The Influence of Digital Supply Chain Technology on Retail Performance - Mashita Ayuni; Immanuel Zai (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of supply chain digitalization on retail performance using supermarkets as the research object. The research method used includes quantitative analysis. This study used Google Forms to create a questionnaire using a Likert scale. The survey received 274 responses, and the data were also analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study concluded that digitalization, supply chain management, and implementation technology have a positive effect on retail performance by linking supply chain performance mediation.